Study on Environmental Management Accounting and Environmental Performance - Rapiah Mohamed; Che Zuriana Muhammad Jamil (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
Research Highlights: The purpose of this paper is to look into the relationship between environmental management accounting (EMA) and environmental performance in Malaysia’s small-medium (SMEs) sized manufacturing sector. The environmental issue has impacted many businesses, regardless of their size or type. Ferreira et al. [1] argue that the company’s size does not determine the application of EMA technique but is determines by the type of industry. EMA practises entail the tracking, tracing, and treatment of costs, earnings, and savings incurred as a result of the company’s environmental activities [2]. EMA is still relatively new in Malaysia, and managers and accountants lack knowledge in this area [3]. As a result, more empirical evidence on EMA practises is required, particularly in developing countries such as Malaysia. As a result, this study is critical in explaining the current practise of EMA in SMEs and its impact on environmental performance. The results show that the physical EMA has a higher mean than the monetary EMA. The findings indicate that the level of EMA practises is not encouraging. According to the regression results, both types of EMA practises (monetary and physical) have a significant impact on environmental performance.